NON-ENGLISH MAJOR TEACHERS' EXPERIENCES OF TEACHING ENGLISH FOR YOUNG LEARNERS (TEYL): A PHENOMENOLOGICAL STUDY - Romadhon, M.Galuh Elga; Dzulfikri, Dzulfikri; Ubaidillah, M. Faruq (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Non-English major teachers’ experiences of teaching English for young learners in Indonesia have not been widely studied until recent times. To fill the lacuna, this phenomenological study looks at the lived experiences of four teachers with non-English major backgrounds who teach English for young learners. Semi-structured interviews were conducted with the participants and teaching observations were also additionally carried out to triangulate the data. The data were then analyzed following Braun and Clarke’s (2006) thematic analysis. Findings suggest that the participating teachers encountered multi-level complexities in teaching English such as wording arrangement, sentence construction, spelling, mother tongue fossilization, and misbelief of English as a foreign language. The study also revealed the use of digital tools, songs, and games, as mostly utilized by the teachers. Interestingly, despite the non-English major backgrounds attached to the teachers, their teachings led to sustained and engaging English language learning among young learners. This study implies that pedagogical decisions have been of value to effective pedagogy and classroom activities in teaching English for young learners.